Aluminium alloy mmc 2009 - 15% SiCP high fatigue performances aluminium alloy for helicopters application - Laillet, E. (My University, 2021)
In aeronautical field, material selection is the result of regular trade-offs between different criterions that may be conflicting: weight, cost, strength performance, susceptibility to flaws, repairability,… The importance of these criterions will obviously change depending on the application (component) targeted, keeping in mind that light weighted structures remain a basic criterion for flying products. In order to minimize the weight while improving strength characteristics, AIRBUS Helicopters has developed for many years with its suppliers a metallic matrix composite, a 2xxx Aluminum alloy reinforced with 15% Silicium carbide particles, and proposes today many certified components manufactured with this material, on the full range of helicopters. For decades now, AIRBUS Helicopters has gathered a huge manufacturing and in-service experience, showing the relevance of this very specific and particular material for the retained applications, and confirming the pertinence of the choice.